Core Protein-Coding Sequence, but Not Core Protein, Modulates the Efficiency of Cap-Independent Translation Directed by the Internal Ribosome Entry Site of Hepatitis C Virus - Wang, Ting-Hsien (American Society for Microbiology, 2000)
Among a myriad of putative functions assigned to the hepatitis C virus (HCV) core protein, several studies suggest that it may modulate internal ribosome entry site (IRES)-mediated initiation of translation. We compared the translational activity of dicistronic reporter transcripts containing the HCV IRES within the intercistronic space fused to downstream sequence encoding either 22 amino acids (aa) or 173 aa of the core protein. The inclusion of the nearly full-length core protein-coding sequence significantly suppressed translation in vitro and in transfected HepG2 cells. However, this suppression was not eliminated by frameshift mutations introduced into the core sequence, suggesting that it occurred at the RNA level and not as a result of core protein expression in cis. Similarly, the expression of core protein (aa 1 to 191) in trans from a recombinant baculovirus did not suppress IRES-directed translation from any of these transcripts in transfected Huh-7 cells. While core protein expression did decrease IRES activity in HepG2 cells (up to 79% suppression), the expression of β-galactosidase from a control baculovirus also suppressed IRES activity (up to 56%), strongly suggesting that this suppression was nonspecific. Finally, the addition of purified recombinant core protein (aa 1 to 179) to in vitro translation reactions at concentrations up to a 10-fold molar excess over the RNA transcripts resulted in no significant reduction in IRES activity. Consistent with these results, a gel retention assay indicated no difference in the affinities of the recombinant HCV core protein and a recombinant Venezuelan equine encephalitis virus capsid protein for HCV IRES-containing RNA transcripts. We conclude that while the inclusion of core protein-coding sequence downstream of the IRES may reduce the efficiency of cap-independent translation on HCV RNA, the core protein itself has no biologically relevant activity in modulating HCV IRES activity.